Effect of Eye Exercise Therapy on Asthenopia Symptoms Among Islamic Boarding School Students in Cirebon: A Quasi-Experimental Study - Rusdiatin, Ivana Eko; Maulana, Darmasta; Nurrohmah, Hasna (Poltekkes Kemenkes Palu, 2025)
Background: There are 2.2 billion people worldwide experiencing eye disorders, with 510 million suffering from untreated vision impairment, and Indonesia is a significant contributor to this issue. Asthenopia is a symptom caused by eye strain, which can lead to vision impairment. This study aims to assess the effect of eye exercise therapy on symptom of asthenopia. Methods: This research was a quasi-experimental study with a non-equivalent pretest-posttest control group design. The study was conducted at the As-Sunnah Islamic Boarding School in Cirebon, West Java for two months, involving 40 students selected based on inclusion criteria. Subjects were given the Visual Fatigue Index Questionnaire to assess symptoms of asthenopia. Ethical approval was obtained from the Ethics Committee of the Faculty of Pharmacy, YPIB University, No. 111/KEP/EC/IV/2024. Informed consent was provided by the subjects through a 35-item consent form. Results: Eye exercise therapy has a significant effect on asthenopia symptoms, as evidenced by the Paired Sample T-Test results (p value < 0.05.with the average Visual Fatigue Index (VFI) score decreasing from 0.49 (pre-test) to 0.37 (post-test) in the intervention group, while the control group showed no significant change (0.48 pre-test to 0.49 post-test). Conclusion: Eye exercise therapy has an effect on Asthenopia symptoms. Future research is recommended to explore the use of eye exercise therapy for refractive eye disorders.